Sexual Interests of Child Sexual Exploitation Material (CSEM) Consumers: Four Patterns of Severity Over Time - Fortin, Francis (International journal of offender therapy and comparative criminology, 2019)
This study analyzed the evolution over time of the activity of consumers of child sexual exploitation material (CSEM). To this end, images and metadata were extracted from the hard drives of 40 individuals convicted of possession of child pornography and analyzed. A sample of these images (N = 61,244) was categorized by the age of the subjects depicted and—using the Combating Paedophile Information Networks in Europe (COPINE) scale—by severity of the acts depicted. Collecting activity was observed to follow four patterns. The most prevalent pattern was a progressive decrease in the age of the person depicted and a progressive increase in the severity of the sexual acts. In light of the results, we propose four explanations of the nature of, and variations in, child-pornography collections.